Chloroquine and Sulfadoxine–Pyrimethamine Resistance in Sub-Saharan Africa—A Review - Roux, Alexandra T. (Front Genet, 2021)
Malaria is a great concern for global health and accounts for a large amount of morbidity and mortality, particularly in Africa, with sub-Saharan Africa carrying the greatest burden of the disease. Malaria control tools such as insecticide-treated bed nets, indoor residual spraying, and antimalarial drugs have been relatively successful in reducing the burden of malaria; however, sub-Saharan African countries encounter great challenges, the greatest being antimalarial drug resistance. Chloroquine (CQ) was the first-line drug in the 20th century until it was replaced by sulfadoxine–pyrimethamine (SP) as a consequence of resistance. The extensive use of these antimalarials intensified the spread of resistance throughout sub-Saharan Africa, thus resulting in a loss of efficacy for the treatment of malaria. SP was replaced by artemisinin-based combination therapy (ACT) after the emergence of resistance toward SP; however, the use of ACTs is now threatened by the emergence of resistant parasites. The decreased selective pressure on CQ and SP allowed for the reintroduction of sensitivity toward those antimalarials in regions of sub-Saharan Africa where they were not the primary drug for treatment. Therefore, the emergence and spread of antimalarial drug resistance should be tracked to prevent further spread of the resistant parasites, and the re-emergence of sensitivity should be monitored to detect the possible reappearance of sensitivity in sub-Saharan Africa.